2020
DOI: 10.1136/bmj.m2519
|View full text |Cite
|
Sign up to set email alerts
|

Freeze-all versus fresh blastocyst transfer strategy during in vitro fertilisation in women with regular menstrual cycles: multicentre randomised controlled trial

Abstract: ObjectiveTo compare the ongoing pregnancy rate between a freeze-all strategy and a fresh transfer strategy in assisted reproductive technology treatment.DesignMulticentre, randomised controlled superiority trial.SettingOutpatient fertility clinics at eight public hospitals in Denmark, Sweden, and Spain.Participants460 women aged 18-39 years with regular menstrual cycles starting their first, second, or third treatment cycle of in vitro fertilisation or intracytoplasmic sperm injection.InterventionsWomen were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
95
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(103 citation statements)
references
References 32 publications
7
95
1
Order By: Relevance
“…A recent multicenter RCT conducted in Europe investigated the effect of freeze‐all and fresh blastocyst ET strategies with a gonadotropin releasing hormone agonist used to trigger final oocyte maturation among 460 women with regular menstrual cycles (mean age of participants 32.4 years in the freeze‐all group and 32.3 years in fresh ET group) demonstrated that the ongoing pregnancy rate, live birth rate, and obstetric and neonatal complications did not differ between the two groups. The study concluded that their findings warrant caution in the indiscriminate application of a freeze‐all strategy when there is no apparent risk of OHSS 10 …”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A recent multicenter RCT conducted in Europe investigated the effect of freeze‐all and fresh blastocyst ET strategies with a gonadotropin releasing hormone agonist used to trigger final oocyte maturation among 460 women with regular menstrual cycles (mean age of participants 32.4 years in the freeze‐all group and 32.3 years in fresh ET group) demonstrated that the ongoing pregnancy rate, live birth rate, and obstetric and neonatal complications did not differ between the two groups. The study concluded that their findings warrant caution in the indiscriminate application of a freeze‐all strategy when there is no apparent risk of OHSS 10 …”
Section: Discussionmentioning
confidence: 97%
“…Supraphysiological hormonal environment in fresh ET cycles might affect endometrial receptivity and implantation rate 7 . However, clinical evidence on the effect of a freeze‐all strategy for women with regular menstrual cycles is conflicting 8‐10 . A recently published meta‐analysis including 11 randomized controlled trials (RCTs) with 5379 patients reported that freeze‐all and subsequent elective FET demonstrated that importantly, neither the live birth rate (relative risk, RR 1.03, 95% confidence interval [CI], 0.91‐1.17) in the subgroup of normal responders nor the cumulative live birth rate in the entire population (RR 1.04, 95% CI, 0.97‐1.11) were significantly different between the two groups 7 .…”
Section: Discussionmentioning
confidence: 99%
“…The contribution of frozen cycles to cumulative live birth rate was not investigated in this trial, but both dosing approaches were associated with supernumerary blastocysts after stimulation and transfer in the fresh cycle. Knowledge about patient preferences and experiences, including reasons for not pursuing further care or cycles, are important for meeting the needs of the patients, and time to pregnancy plays a critical role in this context (Roque and Simon, 2020;Stormlund et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Another important outcome when comparing two different ART strategies, is the time to pregnancy (TTP). Unfortunately, few studies have focused on this matter so far (Stormlund et al, 2020;Vuong et al, 2018b), reporting an increase in the TTP in the freeze-all approach. Based on these findings, it seems inappropriate to implement the freeze-all strategy in all patients undergoing ART, and we will try, hereafter, to discuss the clinical scenarios in which the freeze-all could offer an improvement in terms of pregnancy outcomes or safety.…”
Section: What Impact On the Live Birth Rates?mentioning
confidence: 99%
“…Regarding the patients' perspective, one could suppose that couples would naturally opt for the ET strategy minimizing their time to pregnancy, therefore favoring the fresh ET approach (Stormlund et al, 2020;Vuong et al, 2018b). Surprisingly, in a cohort study of 165 patients focusing on their preferences about the ET strategy (Stormlund et al, 2019), the freeze-all strategy was favored by most.…”
Section: Suggestions For Clinical Practicementioning
confidence: 99%